Web science: An Interdisciplinary Approach to Understanding the Web. - HENDLER, JAMES; SHADBOLT, NIGEL; HALL, WENDY; BERNERS-LEE, TIM; WEITZNER, DANIEL (Communications of the ACM, 2008)
The article discusses the World Wide Web, using an interdisciplinary approach to study the social and technical challenges facing the Web as well as to understand the impact of the Web on society. The authors indicate that a systems approach is necessary to both create and understand the Web of the future. Topics include courses on Web scripting languages, the underlying principles of the Web, and social interactions enabled by the Web. Also discussed are a review of Web-related research and architectural and data requirements of large-scale Web applications.